URGENSI PENDIDIKAN MULTIKULTURAL DALAM MENJAGA NKRI - Mukhamad, Himawan (Al-Munqidz : Jurnal Kajian Keislaman, 2020)
Multicultural education is the process of developing all human potential that respects their plurality and heterogeneity as a consequence of cultural, ethnic, ethnic, and religious (religious) diversity. Multicultural education emphasizes a philosophy of cultural pluralism into the education system based on the principles of equality, mutual respect and acceptance as well as understanding and a moral commitment to social justice. Multicultural education begins with the development of ideas and awareness about interculturalism after World War II.The emergence of interculturalism ideas and awareness is not only related to the development of international politics regarding human rights, independence from colonialism, racial discrimination, etc., also because of the increasing plurality in Western countries themselves as a result of increased migration from newly independent countries to America and Europe. Multicultural education is actually a caring attitude and want to understand (difference) or politics of recognition of political recognition of people from minority groups. Multicultural education looks at society more broadly. Based on the basic view that indifference and non-recognition are not only rooted in racial structural inequality, but the multicultural education paradigm includes subjects regarding injustice, poverty, oppression, and underdevelopment of minority groups in various fields: social, cultural, economic, education , and so forth.The purpose of Islamic education is not limited to filling students' minds with science and subject matter, but to cleanse their souls which must be filled with good character and values and be conditioned so that they can live their lives well. This is in accordance with the objectives of multicultural education, which is to create a harmonious life in a pluralistic society. As a country with a very diverse cultural, ethnic, linguistic andreligious background, Indonesia needs a strategic approach and instrument that can be used as a national movement to realize the unity, unity and integrity of the nation in order to become a sovereign and dignified nation. One of the instruments of its approach is through multicultural education.Multicultural education is a progressive approach to transforming education that holistically provides criticism and shows weaknesses, failures and discrimination in education. Multicultural education as an instrument of social engineering encourages schools to play a role in instilling awareness in multicultural societies and develop tolerance and tolerance to realize the needs and abilities to work with all the differences that exist.The practice of multicultural education in Indonesia can be implemented flexibly, not necessarily in the form of separate or monolithic subjects. The implementation of multicultural education is based on five dimensions: (1) content integration, (2) the process of compiling knowledge, (3) reducing prejudice, (4) equal pedagogy, and (5) school culture and empowering school structures.